PENGARUH ASETILASI TERHADAP PENYERAPAN UAP AIR PADA DUA JENIS KAYU TROPIS - Krisdianto (Jurnal Penelitian Hasil Hutan, 2012)
Acetylation is an esterification process that aiming to replace bydrocyl groups with acetyl groups in the wood. The existence of acetyl group is expected to reduce water adsorption and stabilize wood dimension consequently. This study examined water adsorption on the two acetylated tropical wood species i.e. Anthocephalus chinensis and Calephyllum sp.Using isotherm method. The results show that water adsorption in wood of Antbucephalus is effectively reduced even at the smallest weight percentage gain, while in Calophyllum sp., it is effectively reduced at 10% weight percentage zain. The wuter adsorption varies by the relative humidity and it forms signoid madel from the lowest (11%) to the highest (97) of humidity.